THE PROCESS OF COMMUNICATION PROVIDES OPPORTUNITIES FOR THE PERSONAL DEVELOPMENT OF SCHOOLCHILDREN (Web of Teachers: Inderscience Research, 2025)
This article examines the opportunities for personal growth of secondary school students in the process of communication.